The slow regard of silent things - Rothfuss, Patrick, 1973- (Rothfuss, Patrick, 1973- Kingkiller chronicle., 2014)
Deep below the University, there is a dark place. Few people know of it: a broken web of ancient passageways and abandoned rooms. A young woman lives there, tucked among the sprawling tunnels of the Underthing, snug in the heart of this forgotten place. Her name is Auri, and she is full of mysteries.